Comparison of two techniques of harvesting connective tissue and its effects on healing pattern at palate and recession coverage at recipient site - Nymphea Pandit; Meenakshi Khasa; Shalini Gugnani; Rajvir Malik; Deepika Bali (Wolters Kluwer Medknow Publications, 2016)
Aim: To compare the healing pattern in palate following harvestation of connective tissue graft by two different techniques and to compare the recession coverage at the recipient sites. Materials and Methods: 30 recession sites with Miller's class I and II recession in 16 patients were recruited for this study. Sites were randomly divided into 2 treatment groups. Group I used Unigraft Knife to harvest the connective tissue whereas in group II patients Langer & Langer techniques was used to harvest the connective tissue graft from the palate. Healing was evaluated at the donor site using- wound size(WS), immediate bleeding (iB) and delayed bleeding (dB), complete wound epithelialization (CE), sensibility disorders (S) and post operative pain (PP) at baseline, 1st, 4th, and 12th week postoperatively. Recession coverage was assessed by measuring Clinical Attachment Level (CAL), vertical recession (VR), width of keratinized gingiva (KT). Results: On comparison between Group I and II, a statistically significant larger wound size was observed in Group I. CWE was higher in Group II. A non significant difference was observed when SD, and delayed bleeding were compared at all time intervals. A non-significant difference was observed in the clinical parameters at the recipient site. Conclusion: When evaluating the WS and CWE, the Langer and Langer technique was found to be better than the Unigraft knife technique for harvesting the connective tissue graft, whereas both the techniques were found to be effective in root coverage procedure outcomes.